Garden site south of Keels - Catherwood, Kristin (2012)
An abandoned garden site south of Keels which has become a repository for junk, including what appears to be the rusted-out frame of a vehicle. This site, with its relatively level ground, was formerly a garden which had likely been under cultivation for more than a century when it went out of use sometime late in the twentieth century.